Design of Student Product Sales Application (ETU Market) Using Price Bargaining Feature (Case Study: ETU Polinema) - Alpriansyah, Ilham Okta; Anshori, Moh. Abdullah; Mas’udia, Putri Elfa (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
The author distributed questionnaires to 51 respondents with the results being ineffective in spreading information from friends to friends, distributing pamphlets on campus media, buyers must come to the store, Admin also cannot control sales. The result of this research is an application made in Kotlin language with features that include real time chat between admin, seller and buyer, 1000/km postage feature, bargaining, firebase, API, payment gateway (Midtrans). Comparison of seller location coordinates between the application and Google Maps is 3 digits. Comparison of sending distances using Google maps and servers obtained by customer 1 (0.001 km), customer 2 (0.021 km), customer 3 (0.018 km), customer 4 (0.002 km) and customer 5 (0.047 km). The best delay value for provider A is 8.71 ms (very good), provider B is 35,09 ms (very good) and provider c is 164.52 ms (good). The best throughput value in provider A is 776000 ms (very good), provider B is 11250 ms (very good), and provider C is 14000 ms (very good). The best packet loss value in provider A is 49,7 percent, provider B is 2.4 percent, provider C is 30.3 percent. The maximum distance between the mobile station and the access point is 6 meters.